Jewels of authority : women and textual tradition in Hindu India - Patton, Laurie L., 1961- (Oxford University Press, 2002)
Contributors. Abbreviations. Introduction, Laurie L. Patton. Part II. Ancient Arguments. 1. The Housemistress at the Door: Vedic and Buddhist Perspectives on the Mendicant Encounter, Ellison Banks Findly. 2. Ritual Rights: The Gender Implications of Adhikara, Mary McGee. 3. Mantras and Miscarriage: Controlling Birth in the Late Vedic Period, Laurie L. Patton. Part II. Classical Arguments. 4. Giver or Given? Some Marriages in Kalidasa, Stephanie W. Jamison. 5. Om, the Vedas, and the Status of Women with Special Reference to Srivaisnavism, Katherine K. Young. 6. Casting Light on the Sounds of th.